RoboticA ssistance inS pinalN eurosurgery: A Review - Matthew, Joseph H.; John R. Fitzgerald (Academic Journal of Clinicians, 2024)
Background: Robotic assistance has emerged as a promising technology in thefield of spinal neurosurgery,offering potential benefits in precision, accuracy, and surgical outcomes. This original article investigates the application and efficacy of robotic assistance in spinal neurosurgery, focusing on its utilization in various procedures and its impact on patient outcomes. Methods: A systematic review and meta-analysis were conducted, analyzing relevant studies and clinical data pertaining to robotic-assisted spinal neurosurgery. Key aspects considered include the types of procedures performed with robotic assistance, such as spinal fusion, tumor resection, and minimally invasive surgeries. Patient outcomes, including surgical accuracy, complication rates, and postoperative recovery,were evaluated and compared to conventional techniques. Results: The findings of this original article demonstrate the potential benefits of robotic assistance in spinal neurosurgery. Robotic systems have been successfully utilized in a wide range of procedures, enabling precise instrumentation placement and enhancing surgical accuracy. Improved outcomes, including reduced blood loss, shorter hospital stays, and fewer complications, have been observed in studies utilizing robotic assistance compared to traditional approaches. Conclusion: This original article highlights the potential of robotic assistance as a valuable tool in spinal neurosurgery. The use of robotic systems offers enhanced precision and accuracy, leading to improved surgical outcomes for patients. However, further research and long-term studies are warranted to establish the full extent of the benefits, cost-effectiveness, and long-term outcomes associated with robotic-assisted spinal neurosurgery.